HOW BRAND ENGAGEMENT, BRAND EXPERIENCE ON BRAND LOYALTY THROUGH BRAND TRUST AND BRAND COMMITMENT: SPOTIFY ONLINE MUSIC EVIDENCE - Patria, Danet; Achmadi, Hendra; Wuisan, Dewi; Tampil Purba, John (FEB Universitas Sam Ratulangi Manado, 2023)
In ancient times, humans listened to music using music records in the form of discs that were quite large. Then it developed into smaller discs, then added cassettes and radio. In this modern era, music preservation is received through online applications, and one application that provides these services is Spotify. But this success does not cover the importance of service factors to compete with other brands competitively. Therefore, this study uses quantitative methods to examine the factors influencing consumer loyalty as seen from the community's involvement, experience, Trust, and commitment to the Spotify brand. The Sampling technique uses a non-probability sampling approach. Data was collected using a purposive sampling technique, taking 351 respondents with had experience using the Spotify application. The measurement model for the inner model in this study was analyzed using AMOS 26. In the internal model, testing was discovered by using this study's R2, discriminant, and fitness models. The outer model research includes validity and reliability tests done with SPSS 26 application